2009
DOI: 10.1007/s10529-009-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of enzyme reactors after separation by non-denaturing two-dimensional electrophoresis and immobilization on membrane

Abstract: Activities of carboxylesterase and malate dehydrogenase on membranes were retained after enzymes of mouse liver cytosol were separated by non-denaturing, two-dimensional electrophoresis (2-DE), stained using imidazole and zinc salts and electroblotted on to membranes. Furthermore, hydrolytic changes of phosphatidylcholine by the esterase were examined using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) after separation, and reversible staining and immobilization to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hydrolytic analysis of phosphatidylcholine by carboxylesterase was performed as previously described 9 . In brief, the carboxylesterase on the membrane was incubated in 10 mM Tris-HCl buffer (pH 7.2) containing 25 µg/mL phosphatidylcholine for 30 min at 25°C.…”
Section: Analysis Of Esterase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolytic analysis of phosphatidylcholine by carboxylesterase was performed as previously described 9 . In brief, the carboxylesterase on the membrane was incubated in 10 mM Tris-HCl buffer (pH 7.2) containing 25 µg/mL phosphatidylcholine for 30 min at 25°C.…”
Section: Analysis Of Esterase Activitymentioning
confidence: 99%
“…In addition, because the reduced form of nicotinamide adenine dinucleotide (NADH) and the changes of azo dye can be quantitatively assayed, activities of LDH and esterase can be quantitatively analyzed after separation by non-denaturing electrophoresis [6][7][8] . Furthermore, using non-denaturing electrophoresis, enzymes can be immobilized to the membrane after separation by non-denaturing 2-DE 9,10 . Thus, after enzymes that are reversibly inhibited by…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that a spot at pI 5.5/120,000 is identified as carboxylesterase 1 after proteins in mouse liver cytosol are separated by nondenaturing two-dimensional electrophoresis , and the esterase is immobilized onto membranes [5]. Furthermore, hydrolytic changes of phosphatidylcholine by the esterase are analyzed using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) after the enzyme immobilization [6]. The esterase activity is thought to be inhibited by the tacrine, and the tacrine is thought to be removed by the addition of native chemicals such as aspartic acid.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that cytosolic enzymes can be immobilized on resins or membranes without impairing their activities after extraction, separated by non-denaturing 2-DE and detected by reversible staining [1][2][3]. However, it is difficult to recognize protein spots in the non-denaturing 2-DE gel when proteins are detected by reversible staining.…”
Section: Introductionmentioning
confidence: 99%